Talinghaga developing a board game design for baybayin - Ramos, Patricia Angela B.
Baybayin is a syllabic writing system used widely in ancient Philippine society until its decline during the Spanish invasion. Recently, it has regained popularity due to a renewed interest in calligraphy combined with the general fascination towards Philippine culture.